A Comparative Study of Vaccinated and Non-Vaccinated Covid-19 Cases Against Klebsiella Pneumoniae - SriRajalakshmi, R.; Selvam, K. Panneer (Journal of Neonatal Surgery, 2025)
A Comparative study of COVID- 19 vaccinated individuals against bacterial co-infections could explore valuable insights such as the effectiveness of vaccines in preventing secondary infections, comparative analysis of bacterial infection rates between vaccinated and unvaccinated populations and the COVID-19 vaccines impact the incidence of specific bacterial infections, such as Klebsiella pneumoniae. The start of the COVID-19 pandemic brought about new healthcare challenges, with secondary bacterial infections in hospitalized patients posing additional health threats. In the present cohort study, we analyzed the infection rates of Klebsiella pneumoniae between vaccinated and unvaccinated groups of COVID-19 vaccination for long COVID patients from July 2022 to June 2024. A total of 254 patients in and around Madurai district were collected based on patient demographics such as age, sex, underlying health conditions, vaccination status and district wise distribution of the samples were processed as per standard microbiological techniques